A Population‐Based Evaluation of Quality Indicators for Uterine Cancer Care in Queensland, 2013–2022 - Danny R. Youlden; Helen Hunt; Karen Sanday; Nathan A. Dunn; Penelope M. Webb; Neal Rawson; Victoria Donoghue (Asia-Pacific Journal of Clinical Oncology, 2026)
ABSTRACT Aim To evaluate how diagnostic procedures, treatments, access, and outcomes for uterine cancer have evolved over the last decade using real‐world data. Methods A retrospective cohort study was conducted. Unit record data were sourced from the population‐based Queensland Oncology Repository. Eighteen quality indicators were investigated. Patients with uterine cancer were stratified into two groups according to year of diagnosis (2013–2017 and 2018–2022). Poisson regression and multivariable flexible parametric survival modeling were used to evaluate changes over time, adjusted for key demographic and clinical characteristics. Results The study cohort consisted of 5423 patients. Sentinel lymph node biopsy among patients who had a definitive resection increased dramatically from 14% to 61% (relative likelihood [RL] = 4.24, 95% CI 3.76–4.79; p < 0.001). Use of laparoscopic procedures also increased significantly for both Stages I/II (RL = 1.12, 95% CI 1.08–1.15; p < 0.001) and Stages III/IV (RL = 1.48, 95% CI 1.30–1.68; p < 0.001). The percentage of uterine cancer patients who received a definitive resection within 30 days of diagnosis fell from 56% to 51% (RL = 0.92, 95% CI 0.88–0.97; p = 0.001), with Aboriginal and Torres Strait Islander women faring worse (29%). There was no significant difference in the likelihood of dying within five years of definitive resection by period of diagnosis (adjusted hazard ratio = 0.87, 95% CI 0.74–1.03; p = 0.11). Conclusion Our results have the dual purpose of highlighting opportunities for improvement while also providing benchmarks for the evaluation of uterine cancer care in Queensland into the future.